Body composition and functional fitness capacity of young academy soccer players in South Africa and Zimbabwe - Masocha, V. (2013)
Talent identification and early selection into a professional soccer academy has been reported to be very important for the long term development of footballing expertise (Le Gall et al., 2010). This awareness of the need for early identification of gifted youngsters has led to an increased number of soccer centres of excellence and academies throughout the world. Traditionally, identification and selection of promising individuals into youth soccer academies has been linked to a coach`s subjectivity and preconceived image of the player. Once this method is used in isolation it can result in tedious misjudgements in talent identification - hence the emphasis on science-based approaches. Through soccer-specific research, a number of anthropometric and physical parameters have been linked to successful performance in soccer. The primary aims of the study were to explore the anthropometric, somatotype and functional fitness characteristics of young academy soccer in South Africa and Zimbabwe and to distinguish variables that can be relevant for Talent Identification. The study followed a quantitative non-intervention design with a sample of convenience. A total of 74 young soccer players (Age 15.9±0.81) from South African (n = 41) and Zimbabwean (n = 33) soccer academies were purposively sampled. The following anthropometric variables were measured following the International Society of the Advancement of Kinanthropometry (ISAK) protocol: body mass and height; skinfolds - (triceps, subscapular, biceps, iliac crest, supraspinale, abdominal, front thigh, medial calf); Girths - (arm relaxed, arm flexed and tensed, waist, gluteal, and calf); bone breadths - (biepicondylar humerus and biepicondylar femur). Functional fitness variables that were measured include: lower back muscle flexibility (sit and reach test), upper body flexibility (shoulder flexibility), leg power using (vertical and horizontal jumps), overhead throw (2kg medicine ball throw), speed tests (10, 20, and 40m sprint tests), agility (Illinois test) and aerobic fitness (Hoff test). There were no statistically significant differences in age, body mass, height, fat mass, body mass index, lower back flexibility, right shoulder flexibility, 20m sprint, and endurance capacity (p>0.05). Statistically significant differences were found in percentage body fat (p>0.05), sum of 8 skinfolds, fat free mass, somatotype, left shoulder flexibility, upper and lower body power, 10m and 40m sprints (p<0.01). South African players were found to have higher %BF and sum of skinfolds and then Zimbabwean players. It was concluded that Zimbabwean players performed significantly better than South Africans in agility, 10m, 40m sprints, vertical jump, horizontal jump and overhead throw and had better future chances of success in soccer. Goalkeepers were taller and heavier, while midfielders and defenders were found to be lighter and shorter. Goalkeepers were the most agile group, while forwards were the fastest group. Agility, power and speed were the most important variables that can be used during talent selection and coaches should purposefully work to develop these characteristic during training sessions. Height and weight are relevant in allocating positional roles to players and not in Talent Identification.